FACTORS AFFECTING DEMOGRAPHIC DEVELOPMENT IN AZERBAIJAN AND OPPORTUNITIES TO USE THEM (Научный электронный журнал «Экономика труда и человеческий капитал», 2026)
This study provides a systematic and comprehensive analysis of demographic development in Azerbaijan, with a particular focus on identifying the key structural determinants shaping demographic processes. Drawing on longitudinal data covering the period 1991–2024, the research examines population dynamics, urbanization trends, household structure, age composition, and core demographic indicators within an integrated analytical framework.The findings indicate that Azerbaijan is currently positioned between stages III and IV of the demographic transition, characterized by a sustained decline in fertility, accelerated urbanization, and the early emergence of population aging. The empirical results demonstrate a strong and statistically significant relationship between macroeconomic variables—particularly GDP growth, employment dynamics, and household income levels—and demographic behavior, including fertility decisions, marriage patterns, and migration trends.The scientific novelty of the study lies in the development of a structured classification of demographic determinants, distinguishing between direct and indirect factors and revealing their systemic interdependence. Furthermore, the research provides empirical evidence of a negative relationship between economic growth and natural population increase within the national context, contributing to the ongoing debate on the economic-demographic nexus.By integrating demographic theory with country-specific empirical analysis, the study advances the understanding of demographic transition processes in emerging economies. The results offer important theoretical contributions to demographic economics and provide policy-relevant insights for designing sustainable population, labor market, and social protection strategies in Azerbaijan.